Primary T-cell Non-Hodgkins Lymphoma Presenting as a case of Testicular Mass (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: T-cell lymphoma is a very rare tumor. Only a few cases have been reported in world literature. It involves the testis infrequently, which deserves special attention because of the poor prognosis and the need to make an appropriate diagnosis, which can lead to a better therapeutic strategy.Case presentation: A 34-year-old man presented with left testicular swelling for past four months. The swelling was painless, hard and rubbery. Testicular ultrasound showed diffuse increase in size of the testicle, with alteration in its echogenicity. FNAC was done and the diagnosis was Non-Hodgkins lymphomas. The patient underwent orchidectomy and basing on histopathological and immunohistochemical tests, a peripheral T-cell lymphoma, not otherwise specified was diagnosed.Conclusion: Testicular peripheral T-cell lymphomas are rare and aggressive cancers which is clinically different from seminoma and other non-neoplastic conditions.Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 89-92